Diagnóstico ambiental del ecosistema de la laguna de yambo, cantón Salcedo, provincia Cotopaxi, periodo 2015 - Burgasí Oña, Deisy Alexandra (2016)
The present research it refers to: the “Ecosystem is environmental assessment Yambo Lake, Salcedo Canton, Cotopaxi Province, 2015 period," the study refers to the determination of the levels of contamination and degradation of the natural environment. The general objective is to diagnose the environmental aspect of the ecosystem from Yambo lake, through characterizing environmental factors, to the design of a system base of information, evaluate ecosystem degradation and determine the environmental quality in this place....